Composite material and preparation method thereof, thin film and preparation method thereof, light-emitting device and display device
By modifying inorganic nanomaterials with ester organic matter and organic matter with carboxylic acid groups, the problem of degradation of carrier transfer efficiency caused by surface defects in inorganic nanomaterials is solved, and higher carrier transfer efficiency and chemical stability are achieved. Improved the luminous performance of the light emitting device.
Patent Information
- Application Number
- CN202311031254.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The surface defects of inorganic nanomaterials in existing electroluminescent devices lead to a decrease in carrier transmission efficiency, affecting luminescence performance.
Ester organic matter and organic matter with carboxylic acid groups are used as modification materials to modify the inorganic nanomaterials to form composite materials to passivate surface defects and improve carrier transport efficiency.
Through modification treatment, the carrier transmission efficiency and chemical stability of inorganic nanomaterials are improved, and the luminous performance and service life of the light emitting device are improved.
Smart Images

Figure CN119497508A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of light-emitting devices, and in particular to a composite material and a preparation method thereof, a thin film and a preparation method thereof, a light-emitting device, and a display device. Background Art
[0002] Electroluminescent devices include OLED (Organic Light-Emitting Diode) and QLED (Quantum Dot Light Emitting Diodes). QLED has the advantages of high color saturation, wet process preparation and high stability, which has attracted more and more attention in the research of QLED. OLED has a wide range of applications in display, lighting, smart wearable and other fields due to its good self-luminous properties, high contrast, fast response and flexible display.
[0003] Electroluminescent devices are usually provided with a hole transport layer to improve carrier transport. The hole transport layer can be made of inorganic nanomaterials. However, since inorganic nanomaterials usually have defects on their surfaces, device performance is reduced. Summary of the invention
[0004] Based on this, the embodiments of the present application provide a composite material and a preparation method thereof, a thin film and a preparation method thereof, a light-emitting device, and a display device.
[0005] In a first aspect, an embodiment of the present application provides a composite material, comprising an inorganic nanomaterial and a modification material connected to the surface of the inorganic nanomaterial, wherein the modification material comprises at least one of an ester organic substance and an organic substance having a carboxylic acid group.
[0006] In some embodiments, the organic compound having a carboxylic acid group comprises at least one of a carboxylic acid organic compound and a carboxylate salt; and / or
[0007] The inorganic nanomaterial includes an inorganic hole semiconductor material.
[0008] In some embodiments, the carboxylate comprises an acid ion and a metal ion, wherein the acid ion comprises at least one of 1,3,5-benzenetricarboxylate ion, stearate ion and citrate ion, and the metal ion comprises at least one of silver ion, copper ion, aluminum ion, nickel ion, iron ion and lead ion.
[0009] In some embodiments, the carboxylate comprises at least one of copper phenyl tricarboxylate, silver stearate, and copper citrate; and / or
[0010] The carboxylic acid organic compound includes at least one of 1,3,5-benzenetricarboxylic acid, stearic acid, citric acid and cyclohexanecarboxylic acid; and / or
[0011] The ester organic substance includes ethyl acetate.
[0012] In some embodiments, the mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or
[0013] The inorganic nanomaterial comprises at least one of nickel oxide, cuprous thiocyanate, cuprous iodide, copper oxide, molybdenum trioxide, tungsten trioxide, vanadium pentoxide, chromium trioxide and graphene oxide; and / or
[0014] The inorganic nanomaterial is a nanorod array, and the nanorod array is formed by arranging a plurality of nanorods; and / or
[0015] The average length of the nanorods is 1 μm to 5 μm, and the average diameter of the nanorods is 50 nm to 500 nm.
[0016] In a second aspect, an embodiment of the present application provides a method for preparing a composite material, comprising:
[0017] Obtaining inorganic nanomaterials;
[0018] The inorganic nanomaterial is modified by a modification material to obtain a composite material, wherein the modification material includes at least one of an ester organic substance and an organic substance having a carboxylic acid group.
[0019] In some embodiments, the organic matter having a carboxylic acid group includes at least one of a carboxylic acid organic matter and a carboxylate salt.
[0020] In some embodiments, the carboxylate comprises an acid ion and a metal ion, wherein the acid ion comprises at least one of 1,3,5-benzenetricarboxylate ion, stearate ion and citrate ion, and the metal ion comprises at least one of silver ion, copper ion, aluminum ion, nickel ion, iron ion and lead ion.
[0021] In some embodiments, the carboxylate comprises at least one of copper phenyl tricarboxylate, silver stearate, and copper citrate; and / or
[0022] The carboxylic acid organic compound includes at least one of 1,3,5-benzenetricarboxylic acid, stearic acid, citric acid and cyclohexanecarboxylic acid; and / or
[0023] The ester organic substance includes ethyl acetate.
[0024] In some embodiments, the mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or
[0025] The inorganic nanomaterial comprises at least one of nickel oxide, cuprous thiocyanate, cuprous iodide, copper oxide, molybdenum trioxide, tungsten trioxide, vanadium pentoxide, chromium trioxide and graphene oxide; and / or
[0026] The inorganic nanomaterial is a nanorod array, and the nanorod array is formed by arranging a plurality of nanorods; and / or
[0027] The average length of the nanorods is 1 μm to 5 μm, and the average diameter of the nanorods is 50 nm to 500 nm.
[0028] In some embodiments, when the modification material is an ester compound or a carboxylate, the modification treatment of the inorganic nanomaterial with the modification material includes:
[0029] Mixing the inorganic nanomaterial, the modified material and the first solvent to obtain a mixed system;
[0030] The mixed system is heated and reacted to obtain the composite material.
[0031] In some embodiments, the mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or
[0032] When the inorganic nanomaterial, the modifying material and the first solvent are mixed, the mass ratio of the inorganic nanomaterial, the ester compound and the first solvent is (1-10): (1-3): (5-20); and / or
[0033] When heating the mixed system, the mixed system is heated to 150° C. to 180° C. for 1 hour to 3 hours; and / or
[0034] The first solvent includes at least one of dimethyl sulfoxide, water, dichloromethane and toluene.
[0035] In some embodiments, when the modification material is an ester compound or a carboxylate, the modification treatment of the inorganic nanomaterial with the modification material includes:
[0036] Mixing the inorganic nanomaterial, the modified material and the first solvent to obtain a mixed system;
[0037] The mixed system is heated and reacted to obtain the composite material.
[0038] In some embodiments, when the inorganic nanomaterial, the modifying material and the first solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the first solvent is (1-10): (1-3): (5-20); and / or
[0039] When heating the mixed system, the mixed system is heated to 150° C. to 180° C. for 1 hour to 3 hours; and / or
[0040] The first solvent includes at least one of dimethyl sulfoxide, water, dichloromethane and toluene.
[0041] In some embodiments, when the modification material is a carboxylic acid organic compound, the modification treatment of the inorganic nanomaterial using the modification material includes:
[0042] The inorganic nanomaterial, the modifying material and the second solvent are mixed so that the modifying material modifies the inorganic nanomaterial.
[0043] In some embodiments, when the inorganic nanomaterial, the modifying material and the second solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the second solvent is (1-10): (1-3): (5-20); and / or
[0044] When the modifying material, the inorganic nanomaterial and the second solvent are mixed and reacted, the reaction time is 1 hour to 3 hours; and / or
[0045] The second solvent includes at least one of dimethyl sulfoxide, water, dichloromethane and toluene.
[0046] In a third aspect, an embodiment of the present application provides a film, the material of which includes the composite material as described above or the composite material prepared by the preparation method as described above.
[0047] In a fourth aspect, an embodiment of the present application provides a method for preparing a thin film, comprising:
[0048] A substrate is provided, and a composite material mixed solution is applied on the substrate to obtain the film, wherein the composite material mixed solution comprises a composite material and a third solvent, and the composite material is the composite material as described above or a composite material prepared by the preparation method as described above.
[0049] In some embodiments, the concentration of the composite material mixed solution is 5 mg / ml to 15 mg / ml; and / or
[0050] The third solvent comprises an alcohol compound; and / or
[0051] The alcohol compound includes at least one of methanol, ethanol and isopropanol.
[0052] In some embodiments, the preparation method further comprises: after obtaining the thin film, annealing the thin film, the annealing temperature is 100° C. to 130° C., and the annealing time is 5 minutes to 10 minutes.
[0053] In a fifth aspect, an embodiment of the present application provides a light emitting device, including:
[0054] bottom electrode;
[0055] A hole transport layer, disposed on one side of the bottom electrode, wherein the hole transport layer is the thin film as described above or a thin film prepared by the preparation method as described above;
[0056] A top electrode, disposed on a side of the hole transport layer away from the bottom electrode;
[0057] Wherein, the bottom electrode is a cathode, the top electrode is an anode, and the light-emitting device further comprises a light-emitting layer disposed between the hole transport layer and the bottom electrode; or
[0058] The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device further comprises a light-emitting layer disposed between the top electrode and the hole transport layer.
[0059] In some embodiments, when the bottom electrode is an anode and the top electrode is a cathode, the light-emitting device further comprises an electron transport layer between the light-emitting layer and the top electrode; or
[0060] When the bottom electrode is a cathode and the top electrode is an anode, the light emitting device further comprises an electron transport layer located between the light emitting layer and the bottom electrode;
[0061] The material of the electron transport layer includes at least one of metal oxide, doped metal oxide, II-VI semiconductor material, III-V semiconductor material and I-III-VI semiconductor material, and the metal oxide is selected from ZnO, BaO, TiO 2 SnO 2 At least one of the following; the metal oxide in the doped metal oxide is selected from ZnO, TiO 2 SnO 2 At least one of the doping elements is selected from at least one of Al, Mg, Li, In, and Ga; the II-VI semiconductor material is selected from at least one of ZnS, ZnSe, and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS; and / or
[0062] The bottom electrode and the top electrode are independently selected from a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS or ZnS / Al / ZnS, the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or
[0063] The material of the light-emitting layer includes at least one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene, rubrene derivatives, thermally activated delayed fluorescence materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material comprises at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot each comprise at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, and the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdST e, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, At least one of SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb , at least one of AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from CuInS; 2 、CuInSe 2 AgInS 2 At least one of .
[0064] In a sixth aspect, an embodiment of the present application provides a display device, comprising the light-emitting device as described above.
[0065] The composite material provided in the embodiment of the present application includes an inorganic nanomaterial and a modifying material connected to the surface of the inorganic nanomaterial, wherein the modifying material includes at least one of an ester organic matter and an organic matter having a carboxylic acid group. By modifying the inorganic nanomaterial with the modifying material, the defects on the surface of the inorganic nanomaterial can be passivated, thereby improving the carrier transmission efficiency of the inorganic nanomaterial; and the modifying material can play a certain protective role on the inorganic nanomaterial, thereby improving the chemical stability of the inorganic nanomaterial. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.
[0067] Figure 1 A schematic diagram of the first structure of the light-emitting device provided in an embodiment of the present application.
[0068] Figure 2 A second structural schematic diagram of the light-emitting device provided in an embodiment of the present application.
[0069] Figure 3 A flow chart of a method for preparing a light-emitting device provided in an embodiment of the present application. DETAILED DESCRIPTION
[0070] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.
[0071] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0072] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all mean: a, b, c, a+b, a+c, b+c, or a+b+c, where a, b, c can be single or multiple, respectively.
[0073] In the present application, when another layer is formed "on" a certain layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.
[0074] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0075] An embodiment of the present application provides a composite material, comprising an inorganic nanomaterial and a modification material connected to the surface of the inorganic nanomaterial, wherein the modification material comprises at least one of an ester organic substance and an organic substance having a carboxylic acid group.
[0076] It should be noted that since alkaline substances need to be added as precursors during the preparation process of some inorganic nanomaterials, defect groups will inevitably be introduced on the surface of the inorganic nanomaterials. These defect groups carry negative charges and will quench holes, thereby reducing the hole transmission efficiency, which in turn will affect the carrier balance of the light-emitting device and thus affect the luminescence performance of the light-emitting device.
[0077] It is understood that the defective groups include hydroxyl groups.
[0078] It is understandable that the carboxylic acid compounds generated after the hydrolysis of ester organic matter can combine with the hydroxyl groups on the surface of inorganic nanomaterials, thereby passivating the defects on the surface of inorganic nanomaterials and further improving the hole transport performance of inorganic nanomaterials.
[0079] Exemplarily, the organic matter having a carboxylic acid group includes at least one of a carboxylic acid organic matter and a carboxylate salt.
[0080] Exemplarily, the inorganic nanomaterial includes an inorganic hole semiconductor material.
[0081] It is understandable that carboxylic acid organic matter can directly combine with the hydroxyl group on the surface of inorganic nanomaterials, thereby passivating the defects on the surface of inorganic nanomaterials, and the organic part of carboxylic acid organic matter can protect the inorganic nanomaterials, thereby improving the chemical stability of inorganic nanomaterials. It is understandable that when carboxylic acid salts are hydrolyzed, the acid radical ions therein can combine with hydrogen in water to generate carboxylic acid organic matter, and the carboxylic acid organic matter can combine with the hydroxyl group on the surface of inorganic nanomaterials, thereby passivating the defects on the surface of inorganic nanomaterials, and the organic part can protect the inorganic nanomaterials, thereby improving the chemical stability of inorganic nanomaterials, and at the same time, because the metal ions in the carboxylate have good electrical conductivity, the hole transport performance of the inorganic nanomaterials can be improved.
[0082] Exemplarily, the carboxylate includes an acid ion and a metal ion, the acid ion includes at least one of 1,3,5-benzenetricarboxylate ion, stearate ion and citrate ion, and the metal ion includes at least one of silver ion, copper ion, aluminum ion, nickel ion, iron ion and lead ion.
[0083] Illustratively, the carboxylate includes at least one of copper phenyl tricarboxylate, silver stearate, and copper citrate.
[0084] Illustratively, the carboxylic acid organic compound includes at least one of 1,3,5-benzenetricarboxylic acid, stearic acid, citric acid and cyclohexanecarboxylic acid.
[0085] Exemplarily, the ester organic substance includes ethyl acetate.
[0086] Illustratively, in the composite material, the mass ratio of the inorganic nanomaterial to the modifying material is (1-10):(1-3), for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 1:2, 2:3, 1:3, 5:2, 5:3, etc.
[0087] In some embodiments, the mass ratio of the inorganic nanomaterial to the modifying material is (2-3): (1-2).
[0088] Exemplarily, the inorganic nanomaterials include nickel oxide (NiO), cuprous thiocyanate (CuSCN), cuprous iodide (CuI), copper oxide (CuO), molybdenum trioxide (MoO 3 ), tungsten trioxide (WO 3 ), vanadium pentoxide (V 2 O 5 ), chromium trioxide (CrO 3 ) and at least one of graphene oxide. Exemplarily, the shape of the inorganic nanomaterial can be granular, rod-shaped, sheet-shaped or linear, etc.
[0089] Exemplarily, the inorganic nanomaterial is a nanorod array, and the nanorod array is formed by arranging a plurality of nanorods.
[0090] It can be understood that as a one-dimensional nanomaterial, the nanorod array is short in length and straight in longitudinal shape. The built-in electric field formed by the nanorod array on the C-axis can improve the smoothness of hole transmission to a certain extent, avoid energy loss caused by excessive steric hindrance when holes are transmitted in the interface layer, thereby improving the hole transmission efficiency.
[0091] Exemplarily, the average length of the nanorods is 1 μm to 5 μm (e.g., 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.), and the average diameter of the nanorods is 50 nm to 500 nm (e.g., 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.).
[0092] It should be noted that the present application selects nanorods with an average length of 1 μm to 5 μm, which can improve the hole transmission efficiency while reducing the energy loss caused by the carriers during the transmission process, thereby improving the luminous efficiency of the light-emitting device.
[0093] In some embodiments, the inorganic nanomaterial includes a nickel oxide nanorod array, which is composed of a plurality of nickel oxide nanorods. Nickel oxide has the advantages of high carrier mobility, good stability, and easy processing, and can improve the hole transport efficiency of the composite material, thereby promoting carrier balance inside the light-emitting device, thereby improving the luminous efficiency of the light-emitting device.
[0094] Exemplarily, the average length of the nickel oxide nanorods is 1 μm to 5 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0095] Exemplarily, the average diameter of the nickel oxide nanorods is 50 nm to 500 nm, for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.
[0096] In some embodiments, the modifying material is copper phenyl tricarboxylate, CAS No. 51937-85-0, and the molecular formula is C 18 H 6 Cu 3 O 12 , molecular weight is 604.87, and copper phenyl tricarboxylate used in the examples of the present application was purchased from Aladdin Reagent Network.
[0097] It should be noted that when the modified material is copper phenyl tricarboxylate, the carboxylic acid compound generated after the hydrolysis of copper phenyl tricarboxylate can combine with the hydroxyl group on the surface of the inorganic nanomaterial (introduced during the synthesis of the inorganic nanomaterial) to passivate the defects on its surface. At the same time, the introduction of copper with excellent conductive properties can improve the transmission efficiency of hole-end carriers to a certain extent, so that the transmission of electrons and holes matches; at the same time, copper phenyl tricarboxylate, as an organic substance, itself has a certain ability to isolate water and oxygen. Copper phenyl tricarboxylate is wrapped on the surface of the inorganic nanomaterial, which can play a certain protective role on the inorganic nanomaterial, thereby improving the chemical stability of the inorganic nanomaterial and making the inorganic nanomaterial less susceptible to the external environment; in addition, since copper phenyl tricarboxylate is connected to the hydroxyl group on the surface of the inorganic nanomaterial through a chemical bond, that is to say, the connection force between copper phenyl tricarboxylate and the surface of the inorganic nanomaterial is strong. When the inorganic nanomaterial is a nanorod array, copper phenyl tricarboxylate can play a connecting role between multiple nanorods, thereby improving the stability of the nanorod array.
[0098] It should be noted that when the modifying material is silver stearate, the stearic acid generated after the hydrolysis of silver stearate can combine with the hydroxyl groups on the surface of the inorganic nanomaterial, thereby passivating the hydroxyl defects on the surface of the inorganic nanomaterial. At the same time, the introduction of silver with excellent conductive properties can improve the transmission efficiency of hole-end carriers to a certain extent, so that the transmission of electrons and holes matches; at the same time, silver stearate can be wrapped on the surface of the inorganic nanomaterial, which can play a certain protective role on the inorganic nanomaterial, thereby improving the chemical stability of the inorganic nanomaterial.
[0099] It should be noted that when the modified material is copper citrate, the citric acid generated after the hydrolysis of copper citrate can combine with the hydroxyl groups on the surface of the inorganic nanomaterial, thereby passivating the hydroxyl defects on the surface of the inorganic nanomaterial. At the same time, the introduction of copper with excellent conductive properties can improve the transmission efficiency of hole-end carriers to a certain extent, so that the transmission of electrons and holes is matched.
[0100] It should be noted that when the modifying material is ethyl acetate, the acetic acid generated by the hydrolysis of ethyl acetate can combine with the hydroxyl groups on the surface of the inorganic nanomaterial, thereby passivating the hydroxyl defects on the surface of the inorganic nanomaterial.
[0101] It should be noted that when the modifying material is cyclohexanecarboxylic acid, the cyclohexanecarboxylic acid can combine with the hydroxyl groups on the surface of the inorganic nanomaterial, thereby passivating the hydroxyl defects on the surface of the inorganic nanomaterial.
[0102] It should be noted that among the modification materials such as copper phenyl tricarboxylate, silver stearate, copper citrate, ethyl acetate and cyclohexanecarboxylic acid, copper phenyl tricarboxylate can achieve the best modification effect. This is because copper phenyl tricarboxylate can not only passivate the hydroxyl defects on the surface of the inorganic nanomaterial, but also introduce copper with excellent conductive properties, thereby improving the transmission efficiency of hole-end carriers. Moreover, copper phenyl tricarboxylate has a large molecular weight, so that copper phenyl tricarboxylate can be wrapped on the surface of the inorganic nanomaterial, which can protect the inorganic nanomaterial, thereby improving the chemical stability of the inorganic nanomaterial. Moreover, when the inorganic nanomaterial is a nanorod array, copper phenyl tricarboxylate can connect multiple nanorods, thereby enhancing the stability of the nanorod array and avoiding the phenomenon of uneven film layer of the hole transport layer due to nanorod aggregation.
[0103] The composite material provided in the embodiment of the present application includes an inorganic nanomaterial and a modifying material connected to the surface of the inorganic nanomaterial, wherein the modifying material includes at least one of an ester organic matter and an organic matter having a carboxylic acid group. By modifying the inorganic nanomaterial with the modifying material, the defects on the surface of the inorganic nanomaterial can be passivated, thereby improving the carrier transmission efficiency of the inorganic nanomaterial; and the modifying material can play a certain protective role on the inorganic nanomaterial, thereby improving the chemical stability of the inorganic nanomaterial.
[0104] The present application also provides a method for preparing a composite material, comprising:
[0105] Obtaining inorganic nanomaterials;
[0106] The inorganic nanomaterial is modified by a modification material to obtain a composite material, wherein the modification material includes at least one of an ester organic substance and an organic substance having a carboxylic acid group.
[0107] Since the modification materials have been described in detail above, they will not be described again here.
[0108] For example, when the modifying material is an ester compound (such as ethyl acetate, etc.) or a carboxylate (such as copper phenyl tricarboxylate, silver stearate, copper citrate, etc.), "modifying the inorganic nanomaterial with the modifying material" may specifically include:
[0109] Mixing the inorganic nanomaterial, the modified material and the first solvent to obtain a mixed system;
[0110] The mixed system is heated and reacted to obtain a composite material.
[0111] Exemplarily, when the inorganic nanomaterial, the modifying material and the first solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the first solvent is (1-10):(1-3):(5-20), for example, 1:1:5, 1:1:10, 2:1:5, 3:1:5, 2:2:5, 3:2:5, 2:1:10, 3:1:10, 2:2:10, 3:2:10, 10:3:20, 5:2:10, etc.
[0112] In some embodiments, the mass ratio of the inorganic nanomaterial, the modifying material, and the first solvent is (2-3):(1-2):(5-10).
[0113] Exemplarily, when the mixed system is heated, the mixed system is heated to 150°C to 180°C (e.g., 150°C, 160°C, 170°C, 180°C, etc.), and the heating time is 1 hour to 3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc.).
[0114] Exemplarily, the first solvent includes at least one of dimethyl sulfoxide (DMSO), water, dichloromethane and toluene. It is understandable that, since there is water vapor in the air, even if the first solvent is an organic solvent other than water, the water vapor in the air can still enter the mixed system and provide hydrogen ions and hydroxyls required for the hydrolysis of the modified material.
[0115] Exemplarily, when the inorganic nanomaterial is a nickel oxide nanorod, "obtaining an inorganic nanomaterial" may specifically include: weighing 5-10 mg of nickel nitrate and dissolving it in 20-30 ml of deionized water, stirring evenly to a green transparent solution, adding 2 mg of urea and 0.05-0.1 mg of PF6 (1-butyl-3-methylimidazolium hexafluorophosphate) in sequence, and continuing to stir. Then put it into a reactor, seal the hydrothermal reactor and put it into a constant temperature box, keep it at 150-200°C for 10-20h, cool the product to room temperature, wash it alternately with deionized water and anhydrous ethanol several times, and dry it at 60°C for 24h. Finally, a green product, i.e., a nickel oxide nanorod precursor, is obtained. The dried precursor nanorod is placed in a quartz boat, then transferred to a tube furnace, calcined under air conditions, raised to 700°C at a heating rate of 1°C / min, and kept at 700°C for 5h, and then washed and dried to obtain nickel oxide nanorods.
[0116] For example, when the modifying material is copper phenyl tricarboxylate, “modifying the inorganic nanomaterial with the modifying material” may specifically include:
[0117] 20-30 mg of the prepared nickel oxide nanorods are mixed with 10-20 mg of copper phenyl tricarboxylate and 50-100 ml of dimethyl sulfoxide (DMSO), stirred evenly, and then heated to 150-180° C. for 1-3 hours. The reaction system is dried at 60° C. to 120° C. to obtain nickel oxide nanorods modified with copper phenyl tricarboxylate. The obtained nickel oxide nanorods modified with copper phenyl tricarboxylate can be dispersed in ethanol to prepare a 5-15 mg / ml composite solution for standby use.
[0118] For example, when the modification material is a carboxylic acid organic substance (such as cyclohexanecarboxylic acid, etc.), "modifying the inorganic nanomaterial with the modification material" may specifically include:
[0119] The inorganic nanomaterial, the modifying material and the second solvent are mixed so that the modifying material modifies the inorganic nanomaterial.
[0120] Exemplarily, when the inorganic nanomaterial, the modifying material and the second solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the second solvent is (1-10):(1-3):(5-20), for example, 1:1:5, 1:1:10, 2:1:5, 3:1:5, 2:2:5, 3:2:5, 2:1:10, 3:1:10, 2:2:10, 3:2:10, 10:3:20, 5:2:10, etc.
[0121] In some embodiments, the mass ratio of the inorganic nanomaterial, the modifying material, and the first solvent is (2-3):(1-2):(5-10).
[0122] Exemplarily, when the inorganic nanomaterial, the modifying material and the second solvent are mixed and reacted, the reaction time is 1 hour to 3 hours (eg, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc.).
[0123] Illustratively, the second solvent includes at least one of dimethyl sulfoxide, water, dichloromethane, and toluene.
[0124] See also Figure 1 and Figure 2 The embodiment of the present application provides a light-emitting device 100, including a bottom electrode 70, a hole transport layer 50 and a top electrode 10, wherein the hole transport layer 50 is disposed on one side of the bottom electrode 70, and the hole transport layer 50 is a thin film in any of the above embodiments; the top electrode 10 is disposed on a side of the hole transport layer 50 away from the bottom electrode 70.
[0125] See also Figure 1 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, the light-emitting device 100 further includes a light-emitting layer 40 disposed between the top electrode 10 and the hole transport layer 50 .
[0126] See also Figure 2 When the bottom electrode 70 is a cathode and the top electrode 10 is an anode, the light-emitting device 100 further includes a light-emitting layer 40 disposed between the hole transport layer 50 and the bottom electrode 70 .
[0127] Please combine Figure 1 and Figure 2 The light emitting device 100 may further include a substrate 80, which may be disposed on a side of the bottom electrode 70 away from the light emitting layer 40; illustratively, the material of the substrate 80 may be glass. Figure 1 As shown, when the bottom electrode 70 is an anode, the light emitting device 100 is a positive device; Figure 2 As shown, when the bottom electrode 70 is a cathode, the light emitting device 100 is an inverted device.
[0128] For example, the light emitting device 100 may be a top emitting device (light is emitted toward the side of the light emitting layer 40 away from the substrate 80 ) or a bottom emitting device (light is emitted from the side of the substrate 80 away from the light emitting layer 40 ).
[0129] See also Figure 1 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, the light emitting device 100 further includes an electron transport layer 20 located between the light emitting layer 40 and the top electrode 10 .
[0130] See also Figure 2 When the bottom electrode 70 is a cathode and the top electrode 10 is an anode, the light emitting device 100 further includes an electron transport layer 20 located between the light emitting layer 40 and the bottom electrode 70 .
[0131] Exemplarily, the material of the electron transport layer 20 includes at least one of metal oxide, doped metal oxide, II-VI semiconductor material, III-V semiconductor material and I-III-VI semiconductor material, wherein the metal oxide is selected from ZnO, BaO, TiO 2 SnO 2 At least one of the following; the metal oxide in the doped metal oxide is selected from ZnO, TiO 2 SnO 2 At least one of the doping elements is selected from at least one of Al, Mg, Li, In, and Ga; the II-VI semiconductor group material is selected from at least one of ZnS, ZnSe, and CdS; the III-V semiconductor group material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.
[0132] Exemplarily, the bottom electrode 70 and the top electrode 10 are independently selected from a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, wherein the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS or ZnS / Al / ZnS, the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba.
[0133] Exemplarily, the material of the light-emitting layer 40 includes at least one of an organic light-emitting material and a quantum dot light-emitting material, wherein the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene, rubrene derivatives, thermally activated delayed fluorescence materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material comprises at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot each comprise at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, and the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdST e, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, At least one of SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb , at least one of AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from CuInS; 2 、CuInSe 2 AgInS 2 At least one of .
[0134] In some embodiments, the material of the light-emitting layer 40 is core-shell quantum dots, the core of the core-shell quantum dots is CdZnSeS, CdZnSe, CdSe or CdS, and the shell of the core-shell quantum dots is ZnS, ZnSe or CdS.
[0135] Exemplarily, the thickness of the hole transport layer 50 is 30 nm-50 nm, for example, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm, 50 nm, etc.
[0136] Exemplarily, the thickness of the light emitting layer 40 is 20 nm-50 nm, for example, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm, 50 nm, etc.
[0137] Exemplarily, the thickness of the electron transport layer 20 is 20 nm-50 nm, for example, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm, 50 nm, etc.
[0138] Illustratively, the thickness of each of the bottom electrode 70 and the top electrode 10 is 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, etc.
[0139] See also Figure 3 , see also Figure 1 to Figure 2 The present application embodiment provides a method for preparing a light-emitting device, which is used to prepare the light-emitting device 100 of any of the above embodiments. The method for preparing the light-emitting device includes:
[0140] S100 , providing a light emitting device preform, wherein the light emitting device preform includes a bottom electrode 70 .
[0141] See also Figure 2 When the bottom electrode 70 is a cathode and the top electrode 10 is an anode, the light-emitting device preform further includes an electron transport layer 20 formed on the bottom electrode 70 and a light-emitting layer 40 formed on the electron transport layer 20 .
[0142] See also Figure 1 or Figure 2 The light emitting device preform may further include a substrate 80 disposed on one side of the bottom electrode 70 .
[0143] S200, forming a hole transport layer 50 on the light emitting device preform, wherein the material of the hole transport layer 50 includes an inorganic nanomaterial modified by a modifying material, wherein the modifying material includes at least one of an ester organic substance and an organic substance having a carboxylic acid group.
[0144] S300 , forming a top electrode 10 on the hole transport layer 50 to obtain a light emitting device 100 .
[0145] See also Figure 1When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, “forming the top electrode 10 on the hole transport layer 50 ” may specifically include: forming the light-emitting layer 40 on the hole transport layer 50 , and forming the top electrode 10 on the light-emitting layer 40 .
[0146] See also Figure 1 “Forming a hole transport layer 50 on the light-emitting device preform” may specifically include: applying a hole transport material solution on the light-emitting device preform to form the hole transport layer 50, wherein the hole transport material solution includes an inorganic nanomaterial modified with a modifying material and a third solvent.
[0147] Exemplarily, the concentration of the hole transport material solution is 5 mg / ml to 15 mg / ml, for example 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml, 11 mg / ml, 12 mg / ml, 13 mg / ml, 14 mg / ml, 15 mg / ml, etc.
[0148] Exemplarily, the third solvent includes an alcohol compound. Exemplarily, the alcohol compound includes at least one of methanol, ethanol and isopropanol.
[0149] Exemplarily, "forming a hole transport layer 50 on a light-emitting device preform" may further specifically include: after forming the hole transport layer 50, annealing the hole transport layer 50, the annealing temperature being 100°C to 130°C (for example, 100°C, 110°C, 120°C, 130°C, etc.), and the annealing time being 5 minutes to 10 minutes (for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc.).
[0150] It should be noted that the purpose of annealing the hole transport layer 50 is, on the one hand, to volatilize the third solvent in the hole transport material solution, and on the other hand, to promote a closer combination of the hole transport layer 50 and the light-emitting device preform to achieve connection stability between the film layers.
[0151] See also Figure 1 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, “forming a top electrode 10 on the hole transport layer 50 ” may specifically include: after forming the light-emitting layer 40 on the hole transport layer 50 , forming an electron transport layer 20 on the light-emitting layer 40 , and forming a top electrode 10 on the electron transport layer 20 .
[0152] In some embodiments, the material of the electron transport layer 20 is zinc oxide. In this case, the preparation method of the electron transport layer 20 may include:
[0153] (1) preparing a zinc oxide solution by a sol-gel method, specifically comprising: first preparing 10-30 ml of a 0.5-2 mol / L tetramethylammonium hydroxide ethanol solution, adding dropwise to 5-20 ml of a 0.1-0.5 mol / L zinc acetate dimethyl sulfoxide solution at room temperature, and continuously stirring for 1-2 hours after the dropwise addition is completed to obtain a zinc oxide solution;
[0154] (2) 5-10 ml of zinc oxide solution is mixed with 10-20 ml of ethyl acetate, and centrifuged at a rate of 3000-5000 rpm for 3-5 min. The centrifugation is repeated three times, and the lower precipitate is zinc oxide nanoparticles;
[0155] (3) dispersing zinc oxide nanoparticles in ethanol to prepare a zinc oxide ethanol solution with a concentration of 20-30 mg / ml;
[0156] (4) Using a pipette, 30-50 μl of zinc oxide ethanol solution is slowly dripped onto the light-emitting layer 40 (upright device) or the bottom electrode 70 (inverted device) for spin coating at a speed of 3000-5000 rpm for 20-40 seconds to obtain a zinc oxide layer, which is then annealed at a temperature of 120-160° C. for 10-20 minutes.
[0157] In some embodiments, the material of the light-emitting layer 40 is quantum dots. In this case, the preparation method of the light-emitting layer 40 may include:
[0158] (1) dispersing quantum dots in a solvent (e.g., n-octane) to prepare a quantum dot solution with a concentration of 10-30 mg / ml;
[0159] (2) Use a pipette to take 30-60 μl of quantum dot solution and drop it on the hole transport layer 50 (upright device) or the electron transport layer 20 (inverted device), and then spin coat the solution at a speed of 2000-5000 rpm for 30-60 seconds. Then, anneal the solution at a temperature of 100-150° C. for 5-20 minutes.
[0160] In some embodiments, the bottom electrode 70 is an anode, the top electrode 10 is a cathode, the material of the anode is indium tin oxide (ITO), and the cathode is a laminated structure of metal copper and metal silver (Cu / Ag). In this case, the preparation method of the top electrode 10 may include:
[0161] (1) Place the device into the vacuum coating machine and draw the vacuum to 4×10 -6 mbar, the copper target is first evaporated during evaporation. The metal copper with a thickness of 5-10nm is evaporated at a rate of
[0162] (2) Then open the silver target to Depositing metallic silver with a thickness of 20-50 nm at a rate of 1000 nm to obtain a top electrode 10;
[0163] (3) The top electrode 10 is annealed, the annealing temperature is controlled at 130-150° C., and the annealing time is controlled at 5-10 minutes.
[0164] An embodiment of the present application further provides a display device, comprising a light-emitting device 100 manufactured by the method for manufacturing a light-emitting device in any of the above embodiments or the light-emitting device 100 in any of the above embodiments.
[0165] The light emitting device 100 and the manufacturing method thereof according to the embodiment of the present application are described in detail in the form of specific embodiments below.
[0166] Example 1
[0167] A composite material comprises nickel oxide nanorods (inorganic nanomaterials) and copper phenyl tricarboxylate connected to the surface of the nickel oxide nanorod array;
[0168] The preparation method of the composite material comprises: mixing 25 mg of nickel oxide nanorods, 15 mg of copper phenyl tricarboxylate and 75 ml of dimethyl sulfoxide, stirring evenly and heating to 165° C., reacting for 2 hours, drying the reaction system at 80° C. to obtain the composite material, and dispersing the obtained composite material in ethanol to prepare a 10 mg / ml composite material mixed solution for standby use.
[0169] Example 2
[0170] A composite material comprises nickel oxide nanorods (inorganic nanomaterials) and silver stearate connected to the surface of the nickel oxide nanorod array;
[0171] The preparation method of the composite material comprises: mixing 25 mg of nickel oxide nanorods, 15 mg of silver stearate and 75 ml of dimethyl sulfoxide, stirring evenly, heating to 165° C., reacting for 2 hours, drying the reaction system at 80° C. to obtain the composite material, and dispersing the obtained composite material in ethanol to prepare a 10 mg / ml composite material mixed solution for standby use.
[0172] Example 3
[0173] A composite material comprises nickel oxide nanorods (inorganic nanomaterial) and copper citrate connected to the surface of the nickel oxide nanorod array;
[0174] The preparation method of the composite material comprises: mixing 25 mg of nickel oxide nanorods, 15 mg of copper citrate and 75 ml of dimethyl sulfoxide, stirring evenly, heating to 165° C., reacting for 2 hours, drying the reaction system at 80° C. to obtain the composite material, and dispersing the obtained composite material in ethanol to prepare a 10 mg / ml composite material mixed solution for standby use.
[0175] Example 4
[0176] A composite material comprises nickel oxide nanorods (inorganic nanomaterials) and ethyl acetate connected to the surface of the nickel oxide nanorod array;
[0177] The preparation method of the composite material comprises: mixing 25 mg of nickel oxide nanorods, 15 mg of ethyl acetate and 75 ml of dimethyl sulfoxide, stirring evenly, heating to 165° C., reacting for 2 hours, drying the reaction system at 80° C. to obtain the composite material, and dispersing the obtained composite material in ethanol to prepare a 10 mg / ml composite material mixed solution for standby use.
[0178] Example 5
[0179] A composite material comprises nickel oxide nanorods (inorganic nanomaterials) and cyclohexanecarboxylic acid connected to the surface of the nickel oxide nanorod array;
[0180] The preparation method of the composite material comprises: mixing 25 mg of nickel oxide nanorods with 15 mg of cyclohexanecarboxylic acid and 75 ml of water, stirring evenly, standing for reaction for 2 hours, drying the reaction system at 80° C. to obtain nickel oxide nanorods modified with cyclohexanecarboxylic acid, and dispersing the obtained nickel oxide nanorods modified with cyclohexanecarboxylic acid in ethanol to form a 10 mg / ml hole transport material solution for standby use.
[0181] Example 6
[0182] like Figure 1 As shown, a light-emitting device 100 is composed of a bottom electrode 70, a hole transport layer 50, a light-emitting layer 40, an electron transport layer 20 and a top electrode 10 which are stacked in sequence, wherein the top electrode 10 is a cathode and the bottom electrode 70 is an anode; the material of the top electrode 10 is Cu / Ag, the material of the electron transport layer 20 is zinc oxide, the material of the light-emitting layer 40 is a core-shell structure quantum dot, the core of the core-shell structure quantum dot is CdZnSeS, the shell of the core-shell structure quantum dot is ZnS, the material of the hole transport layer 50 is the composite material of Example 1, and the material of the bottom electrode 70 is ITO;
[0183] Among them, the thickness of the bottom electrode 70 is 100nm, the thickness of the hole transport layer 50 is 40nm, the thickness of the light-emitting layer 40 is 35nm, the thickness of the electron transport layer 20 is 35nm, the thickness of the top electrode 10 is 42.5nm, the thickness of the Cu layer is 7.5nm, and the thickness of the Ag layer is 35nm.
[0184] The method for preparing the light emitting device 100 includes:
[0185] Provide a glass having a bottom electrode 70 on its surface, wherein the material of the bottom electrode 70 is ITO, clean the glass, wipe the surface of the bottom electrode 70 with a cotton swab dipped in a small amount of soapy water to remove impurities visible to the naked eye, then ultrasonically clean the glass with deionized water, acetone, ethanol, and isopropanol for 15 minutes, and then blow dry the glass with nitrogen for later use;
[0186] 20 ml of hole transport material solution was sucked with a pipette and slowly dripped onto the cleaned glass for spin coating. The rotation speed during spin coating was controlled at 3000 rpm for 20 seconds. The hole transport material solution included nickel oxide nanorod arrays modified with copper phenyl tricarboxylate and ethanol. The concentration of the hole transport material solution was 10 mg / ml. The glass was then transferred to an annealing table for 7.5 minutes at 115° C. to obtain a hole transport layer 50.
[0187] 45 microliters of quantum dot solution is sucked with a pipette and slowly dripped onto the hole transport layer 50 for spin coating. The spin coating speed is 3500 rpm and the time is controlled at 45 seconds. The quantum dot solution includes quantum dots and n-hexane. The concentration of the quantum dot solution is 15 mg / ml. Then, annealing is performed. The annealing temperature is 125° C. and the annealing time is controlled at 12.5 minutes to obtain the light-emitting layer 40.
[0188] 40 microliters of zinc oxide solution is sucked with a pipette and slowly dripped onto the light-emitting layer 40 for spin coating. The spin coating speed is 4000 rpm and the time is controlled within 30 seconds. The zinc oxide solution includes zinc oxide nanoparticles and ethanol. The concentration of the zinc oxide solution is 25 mg / ml. Then, annealing is performed. The annealing temperature is 140° C. and the annealing time is controlled within 15 minutes to obtain the electron transport layer 20.
[0189] Top electrode 10 evaporation: Place the glass into the vacuum coating machine and pump the vacuum to 4×10 -6 mbar, the copper target is first evaporated during evaporation. The copper metal was deposited at a thickness of 7.5 nm at a rate of The cathode was obtained by evaporating metallic silver with a thickness of 35 nm at a rate of 1000 nm; then annealing was performed, the annealing temperature was controlled at 140° C., and the annealing time was controlled at 7.5 minutes.
[0190] Then, glue is coated on the outer surface of the stacked structure consisting of the bottom electrode 70 , the hole transport layer 50 , the light-emitting layer 40 , the electron transport layer 20 and the top electrode 10 , and the glue is cured by ultraviolet irradiation to obtain the light-emitting device 100 .
[0191] Example 7
[0192] A light emitting device 100 and a method for preparing the same are different from those of Example 6 in that the material of the hole transport layer 50 is the composite material in Example 2.
[0193] Example 8
[0194] A light emitting device 100 and a method for preparing the same are different from those of Example 6 in that the material of the hole transport layer 50 is the composite material in Example 3.
[0195] Example 9
[0196] A light emitting device 100 and a method for preparing the same are different from those of Example 6 in that the material of the hole transport layer 50 is the composite material in Example 4.
[0197] Example 10
[0198] A light emitting device 100 and a method for preparing the same are different from those of Example 6 in that the material of the hole transport layer 50 is the composite material in Example 5.
[0199] Embodiment 11
[0200] A light-emitting device 100 and a preparation method thereof, compared with Example 6, the only difference is that when preparing the hole transport layer 50, the concentration of the hole transport material solution used is different, and the thickness of the obtained hole transport layer 50 is different. In Example 5, the concentration of the hole transport material solution used is 5 mg / ml, and the thickness of the hole transport layer 50 is 30 nm.
[0201] Example 12
[0202] A light-emitting device 100 and a preparation method thereof, compared with Example 6, the only difference is that when preparing the hole transport layer 50, the concentration of the hole transport material solution used is different, and the thickness of the obtained hole transport layer 50 is different. In Example 6, the concentration of the hole transport material solution used is 15 mg / ml, and the thickness of the hole transport layer 50 is 50 nm.
[0203] Embodiment 13
[0204] A light emitting device 100 and a preparation method thereof, compared with Example 6, the only difference is that when preparing the hole transport layer 50 for annealing, the annealing temperature and annealing time used are different. In Example 6, the annealing temperature is 100°C and the annealing time is 10 minutes.
[0205] Embodiment 14
[0206] A light emitting device 100 and a preparation method thereof, compared with Example 6, the only difference is that when preparing the hole transport layer 50 for annealing, the annealing temperature and annealing time used are different. In Example 7, the annealing temperature is 130°C and the annealing time is 5 minutes.
[0207] Comparative Example 1
[0208] A light emitting device 100 and a preparation method thereof, compared with Example 6, the only difference is that the material of the hole transport layer 50 is different. In Comparative Example 1, the material of the hole transport layer 50 is unmodified nickel oxide nanorods.
[0209] Performance Testing
[0210] The luminous efficiency (CE) of the light-emitting devices 100 in Examples 1-8 and the light-emitting device 100 in Comparative Example 1 was tested, and the service life (T95@1000nit) of the light-emitting devices 100 in Examples 1-8 and the light-emitting device 100 in Comparative Example 1 was tested, and the results are shown in the following table.
[0211] CE(cd / A) T95@1000nit(h) Example 6 120 4800 Example 7 116 4650 Example 8 118 4700 Example 9 100 4150 Example 10 96 4000 Embodiment 11 115 4500 Example 12 110 4400 Embodiment 13 117 4600 Embodiment 14 118 4650 Comparative Example 1 90 3800
[0212] It can be seen from the above table that the luminous efficiency (CE) of the light-emitting devices 100 of Examples 6-14 of the present application is greater than the luminous efficiency (CE) of the light-emitting device 100 of Comparative Example 1, and the service life (T95@1000nit) of the light-emitting devices 100 of Examples 6-14 of the present application is greater than the service life (T95@1000nit) of the light-emitting device 100 of Comparative Example 1. That is to say, compared with the light-emitting device 100 using the unmodified nickel oxide nanorod array as the hole transport layer 50 in Comparative Example 1, the light-emitting device 100 using the inorganic nanomaterial modified by the modifying material as the hole transport layer 50 in Examples 6-14 of the present application has higher luminous efficiency and longer service life.
[0213] By comparing Examples 6-14, it can be seen that the luminous efficiency (CE) of the light-emitting device 100 of Example 6 is greater than the luminous efficiency (CE) of the light-emitting device 100 of Examples 7-14, and the service life (T95@1000nit) of the light-emitting device 100 of Example 6 is longer than the service life (T95@1000nit) of the light-emitting device 100 of Examples 7-14, which shows that the modification effect of copper phenyl tricarboxylate is better.
[0214] The composite material and its preparation method, thin film and its preparation method, light-emitting device, and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application, and the description of the above embodiments is only used to help understand the present application. At the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present application.
Claims
1. A composite material, characterized in that: The invention comprises an inorganic nano material and a modification material connected to the surface of the inorganic nano material, wherein the modification material comprises at least one of an ester organic substance and an organic substance having a carboxylic acid group.
2. The composite material according to claim 1, characterized in that The organic matter having a carboxylic acid group comprises at least one of a carboxylic acid organic matter and a carboxylate; and / or The inorganic nanomaterial includes an inorganic hole semiconductor material.
3. The composite material according to claim 2, characterized in that The carboxylate comprises an acid ion and a metal ion, wherein the acid ion comprises at least one of 1,3,5-benzenetricarboxylate ion, stearate ion and citrate ion, and the metal ion comprises at least one of silver ion, copper ion, aluminum ion, nickel ion, iron ion and lead ion; and / or The carboxylate comprises at least one of copper phenyl tricarboxylate, silver stearate and copper citrate; and / or The carboxylic acid organic compound includes at least one of 1,3,5-benzenetricarboxylic acid, stearic acid, citric acid and cyclohexanecarboxylic acid; and / or The ester organic substance includes ethyl acetate.
4. The composite material according to claim 1, characterized in that The mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or The inorganic nanomaterial comprises at least one of nickel oxide, cuprous thiocyanate, cuprous iodide, copper oxide, molybdenum trioxide, tungsten trioxide, vanadium pentoxide, chromium trioxide and graphene oxide; and / or The inorganic nanomaterial is a nanorod array, and the nanorod array is formed by arranging a plurality of nanorods; and / or The average length of the nanorods is 1 μm to 5 μm, and the average diameter of the nanorods is 50 nm to 500 nm.
5. A method for preparing a composite material, characterized in that: include: Obtaining inorganic nanomaterials; The inorganic nanomaterial is modified by a modification material to obtain a composite material, wherein the modification material includes at least one of an ester organic matter and an organic matter having a carboxylic acid group.
6. The method for preparing a composite material according to claim 5, characterized in that: The organic matter having a carboxylic acid group comprises at least one of a carboxylic acid organic matter and a carboxylate; and / or The inorganic nanomaterial includes an inorganic hole semiconductor material.
7. The method for preparing a composite material according to claim 6, characterized in that: The carboxylate comprises an acid ion and a metal ion, wherein the acid ion comprises at least one of 1,3,5-benzenetricarboxylate ion, stearate ion and citrate ion, and the metal ion comprises at least one of silver ion, copper ion, aluminum ion, nickel ion, iron ion and lead ion; and / or The carboxylate comprises at least one of copper phenyl tricarboxylate, silver stearate and copper citrate; and / or The carboxylic acid organic compound includes at least one of 1,3,5-benzenetricarboxylic acid, stearic acid, citric acid and cyclohexanecarboxylic acid; and / or The ester organic substance includes ethyl acetate.
8. The method for preparing a composite material according to claim 5, characterized in that: The mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or The inorganic nanomaterial comprises at least one of nickel oxide, cuprous thiocyanate, cuprous iodide, copper oxide, molybdenum trioxide, tungsten trioxide, vanadium pentoxide, chromium trioxide and graphene oxide; and / or The inorganic nanomaterial is a nanorod array, and the nanorod array is formed by arranging a plurality of nanorods; and / or The average length of the nanorods is 1 μm to 5 μm, and the average diameter of the nanorods is 50 nm to 500 nm.
9. The method for preparing a composite material according to claim 6, characterized in that: When the modification material is an ester compound or a carboxylate, the modification treatment of the inorganic nanomaterial using the modification material includes: Mixing the inorganic nanomaterial, the modified material and the first solvent to obtain a mixed system; The mixed system is heated and reacted to obtain the composite material.
10. The method for preparing a composite material according to claim 9, characterized in that: The mass ratio of the inorganic nanomaterial to the modifying material is (1-10): (1-3); and / or When the inorganic nanomaterial, the modifying material and the first solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the first solvent is (1-10): (1-3): (5-20); and / or When heating the mixed system, the mixed system is heated to 150° C. to 180° C. for 1 hour to 3 hours; and / or The first solvent includes at least one of dimethyl sulfoxide, water, dichloromethane and toluene.
11. The method for preparing a composite material according to claim 6, characterized in that: When the modification material is a carboxylic acid organic compound, the modification treatment of the inorganic nanomaterial using the modification material includes: The inorganic nanomaterial, the modifying material and the second solvent are mixed so that the modifying material modifies the inorganic nanomaterial.
12. The method for preparing a composite material according to claim 11, characterized in that: When the inorganic nanomaterial, the modifying material and the second solvent are mixed, the mass ratio of the inorganic nanomaterial, the modifying material and the second solvent is (1-10): (1-3): (5-20); and / or When the modifying material, the inorganic nanomaterial and the second solvent are mixed and reacted, the reaction time is 1 hour to 3 hours; and / or The second solvent includes at least one of dimethyl sulfoxide, water, dichloromethane and toluene.
13. A film, characterized in that: The material of the film includes the composite material according to any one of claims 1 to 4 or the composite material prepared by the preparation method according to any one of claims 5 to 12.
14. A method for preparing a thin film, characterized in that: include: A substrate is provided, and a composite material mixed solution is applied on the substrate to obtain the film, wherein the composite material mixed solution comprises a composite material and a third solvent, and the composite material is the composite material as described in any one of claims 1 to 4 or a composite material obtained by the preparation method as described in any one of claims 5 to 10.
15. The method for preparing a thin film according to claim 14, characterized in that: The concentration of the composite material mixed solution is 5 mg / ml to 15 mg / ml; and / or The third solvent comprises an alcohol compound; and / or The alcohol compound includes at least one of methanol, ethanol and isopropanol.
16. The method for preparing a thin film according to claim 14, characterized in that: The preparation method further comprises: after obtaining the film, annealing the film, the annealing temperature is 100° C. to 130° C., and the annealing time is 5 minutes to 10 minutes.
17. A light emitting device, characterized in that: include: bottom electrode; A hole transport layer, disposed on one side of the bottom electrode, wherein the hole transport layer is a thin film according to claim 13 or a thin film prepared by the preparation method according to any one of claims 14 to 16; A top electrode, disposed on a side of the hole transport layer away from the bottom electrode; Wherein, the bottom electrode is a cathode, the top electrode is an anode, and the light-emitting device further comprises a light-emitting layer disposed between the hole transport layer and the bottom electrode; or The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device further comprises a light-emitting layer disposed between the top electrode and the hole transport layer.
18. The light emitting device according to claim 17, characterized in that: When the bottom electrode is an anode and the top electrode is a cathode, the light emitting device further comprises an electron transport layer between the light emitting layer and the top electrode; or When the bottom electrode is a cathode and the top electrode is an anode, the light emitting device further comprises an electron transport layer located between the light emitting layer and the bottom electrode; The material of the electron transport layer includes at least one of metal oxide, doped metal oxide, II-VI semiconductor material, III-V semiconductor material and I-III-VI semiconductor material, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS; and / or The bottom electrode and the top electrode are independently selected from a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or The material of the light-emitting layer includes at least one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene, rubrene derivatives, thermally activated delayed fluorescence materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material comprises at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot each comprise at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, and the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnS At least one of CdS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, Pb At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, and AlNSb , AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2. ; 19. A display device, characterized in that: Comprising a light emitting device as claimed in any one of claims 17 or 18.